Rapid Credit Growth : Boon or Boom-Bust? - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2011)
Episodes of rapid credit growth, especially credit booms, tend to end abruptly, typically in the form of financial crises. This paper presents the findings of a comprehensive event study focusing on 99 credit booms. Loose monetary policy stances seem to have contributed to the build-up of credit booms across both advanced and emerging economies. In particular, domestic policy rates were below trend during the pre-peak phase of credit booms and likely fuelled macroeconomic and financial imbalances. For emerging economies, while credit booms are associated with episodes of large capital inflows, international interest rates (a proxy for global liquidity) are virtually flat during these periods. Therefore, although external factors such as global liquidity conditions matter, and possibly increasingly so over time, domestic factors (especially monetary policy) also appear to be important drivers of real credit growth across emerging economies.